PEMBERDAYAAN PEREMPUAN MELALUI PEMBUDIDAYAAN TANAMAN SAYURAN DALAM POT BERBASIS APLIKASI TEKNOLOGI BOKASHI ECENG GONDOK - Gusti Irya Ichriani Kambang Vetrani Asie Siti Zubaidah, Dan Syahrudin (Buletin Udayana Mengabdi, 2013)
Vegetables cultivation in the pot based on Eichhornia crassipes bokashi technology application is the activity toempower women synergized with the natural resources around them. The purposed of IbM program implementationwere (1) empower and provide skills to the women group in order to utilize of natural resources (Eichhorniacrassipes, sawdust and alluvial soil) and obtain vitamines, minerals and fiber for households through the vegetablescultivation in the pot and utilization of Eichhornia crassipes bokashi as growing mixture media; (2) as effort tosave on household spending and to creating entrepreneurship. This program was carried out with two groupsof women (the RW I women group and RW II women group) from Cemara Labat, Palangka Raya, Central ofKalimantan. Socialization, training and coaching about cultivation of vegetables in the pot and making of Eichhorniacrassipes bokashi has given the ability and skills to the women group for utilizing natural resources around them.This IbM programme has sustainability. It is caused the women groups from RW I and RW II Cemara Labatwant to continue planting vegetables in the pot using Eichhornia crassipes bokashi, to meet needs of householdvegetables daily and it has raised a family entrepreneurship.